Who Is Poorest? An Asset‐based Analysis of Multidimensional Wellbeing. (January 2015) - Wietzke, Frank‐Borge
<x xml:space="preserve">Abstract</x> Recent studies have endorsed asset‐based approaches as a strategy for attaining the Millennium Development Goals. This article discusses asset indices as a diagnostic tool for these policies, systematically breaking them down into separate dimensions of private household wealth and basic public‐goods access and discussing how shortfalls in public‐goods supply can be related to deprivations in basic human capabilities under the asset framework. It then illustrates how asset indices can be used for the targeting of public infrastructure investments and private asset‐accumulation policies, with the help of a detailed case study of deprivations in household wealth and public‐service supply in Madagascar.